Online epistemic communities: theoretical and methodological directions for understanding knowledge co-elaboration in new digital spaces. - Soares, Marcelo M.; Jacobs, Karen; Détienne, Françoise; Barcellini, Flore; Baker, Michael; Burkhardt, Jean-Marie; Fréard, Dominique (Work)
This paper presents, illustrates and discusses a generic framework for studying knowledge co-elaboration in online epistemic communities ('OECs'). Our approach is characterised by: considering knowledge co-elaboration as a design activity; distinguishing discussion and production spaces in OECs; characterising participation via the notion of role; fine-grained analyses of meaning, content and communicative functions in interactions. On this basis, three key issues for ergonomics research on OECs are discussed and illustrated by results from our previous studies on OSS and Wikipedia. One issue concerns the interrelation between design (task) and regulation. Whereas design task-oriented activity is distributed among participants, we illustrate that OCEs function with specialised emerging roles of group regulation. However, the task-oriented activity also functions at an interpersonal level, as an interplay of knowledge-based discussion with negotiation of competencies. Another issue concerns the foci of activity on the (designed) knowledge object. Based on a generic task model, we illustrate asymmetry and distinctiveness in tasks' foci of participants. The last issue concerns how design-use mediation is ensured by specific forms of mediation roles in OECs. Finally we discuss the degree of generality of our framework and draw some perspectives for extending our framework to other OECs.